2019
DOI: 10.1029/2019wr024954
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Systematic Spatial Variability in the Surface Heat Flux of a Large Lake: A Multiannual Analysis for Lake Geneva

Abstract: The spatiotemporal surface heat flux (SurHF) distribution over Lake Geneva, the largest lake in Western Europe, was estimated for a 7-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014). Data sources included hourly maps of over-the-lake assimilated meteorological data from a validated numerical weather model and lake surface water temperature (LSWT) from satellite imagery. A set of bulk algorithms, previously optimized and calibrated at two locations in Lake Geneva, was used. Results indicate a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Over large lakes, temperature varies with bathymetry due to variable rates of vertical mixing in large lakes -however, this variability only depends on lake bathymetry which can be treated as a static parameter, and heat exchange can be modeled or observed with better accuracy in larger lakes from space observations (as noted before). On the other hand, in a study by Rahaghi et al (2019), it was shown that radiation at the surface of a large Swiss lake (Lake Geneva) varied on the order greater than 40 Wm -2 in different parts of the same lake, which is quite a significant error for a large lake and was attributed to shading effect by clouds, a dynamic error. In terrestrial hydrology, where radiation budget is calculated from temperature (e.g.…”
Section: Can Horton's Evaporation Formula Replace Other Methods?mentioning
confidence: 98%
“…Over large lakes, temperature varies with bathymetry due to variable rates of vertical mixing in large lakes -however, this variability only depends on lake bathymetry which can be treated as a static parameter, and heat exchange can be modeled or observed with better accuracy in larger lakes from space observations (as noted before). On the other hand, in a study by Rahaghi et al (2019), it was shown that radiation at the surface of a large Swiss lake (Lake Geneva) varied on the order greater than 40 Wm -2 in different parts of the same lake, which is quite a significant error for a large lake and was attributed to shading effect by clouds, a dynamic error. In terrestrial hydrology, where radiation budget is calculated from temperature (e.g.…”
Section: Can Horton's Evaporation Formula Replace Other Methods?mentioning
confidence: 98%
“…Those ocean measurements were carried out under upward heat fluxes and thus unstable ABL conditions, whereas our measurements were taken under stable conditions (ζ = 0.93) and net surface warming (Fig. 5a), which is typical for the spring period over Lake Geneva (Rahaghi et al, 2019b). The difference between our measurements and those carried out in the ocean illustrate two mechanisms through which slicks can affect the surface water temperature: In the ocean studies, the reduction of temperature in slicks was associated with the surfactants' ability to suppress The air-side friction velocity is calculated following Zeng et al (1998), accounting for atmospheric boundary layer stability and measurement height;…”
Section: Wave Height Estimatementioning
confidence: 99%
“…Air-water exchange dynamics are different under stable and unstable Atmospheric Boundary layer (ABL) (Kara et al, 2005;Mahrt and Hristov, 2017). Although near surface dynamics under stable ABL conditions have been studied in lakes during events (e.g., Yusup and Liu, 2016;Rahaghi et al, 2019b), their potential differences in slick and non-slick areas under stable ABL and light wind conditions during DWL formation have not yet been reported. However, these differences can strongly affect air-water exchange.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this variability only depends on lake bathymetry which can be treated as a static parameter, and heat exchange can be modeled or observed with better accuracy in larger lakes from space observations (as noted before). On the other hand, in a study by Rahaghi et al (2019), it was shown that radiation at the surface of a large Swiss lake (Lake Geneva) varied of the order of greater than 40 W m −2 in different parts of the same lake, which is quite a significant error for a large lake, and was attributed to shading effect by clouds, which is a dynamic error. In terrestrial hydrology, where the radiation budget is calculated from temperature (e.g., Bohn et al, 2013), Horton's method has a particular advantage.…”
mentioning
confidence: 99%